Changes in the expression of cancer- and metastasis-related genes and proteins after metformin treatment under different metabolic conditions in endometrial cancer cells - Lange, Carsten; Brüggemann, Jana; Thüner, Theresa; Jauckus, Julia; Strowitzki, Thomas; Germeyer, Ariane (Heliyon, 2023)
Research question - Hyperinsulinemia and elevated estrogen levels are known risk factors for endometrial cancer (EC) development and are associated with obesity, type 2 diabetes mellitus (T2DM), insulin resistance, among others. Metformin, an insulin-sensitizing drug, displays anti-tumor effects in cancer patients, including EC, but the mechanism of action is still not completely understood. In the present study, the effects of metformin on gene and protein expression were investigated in pre- and postmenopausal EC in vitro models in order to identify candidates that are potentially involved in the drug's anti-cancer mechanism. - Design - After treating the cells with metformin (0.1 and 1.0 mmol/L), changes in the expression of >160 cancer- and metastasis-related gene transcripts were evaluated with RNA arrays. A total of 19 genes and 7 proteins were selected for a follow-up expression analysis, including further treatment conditions, in order to evaluate the influence of hyperinsulinemia and hyperglycemia on metformin-induced effects. - Results - Changes in the expression of BCL2L11, CDH1, CDKN1A, COL1A1, PTEN, MMP9 and TIMP2 were analyzed on gene and protein level. The consequences resulting from the detected expression changes as well as the influence of varying environmental influences are discussed in detail. With the presented data, we contribute to a better understanding of the direct anti-cancer activity of metformin as well as its underlying mechanism of action in EC cells. - Conclusions - Although further research will be necessary to confirm the data, the influence of different environmental settings on metformin-induced effects could be highlighted with the presented data. Additionally, gene and protein regulation were not similar in the pre- and postmenopausal in vitro models.
Online verfügbar: 25. Mai 2023, Artikelversion: 2. Juni 2023
Gesehen am 17.08.2023